THE STUDY OF WOMEN AND CHILD HEALTH (International Journal of Food and Nutritional Sciences, 2022)
My paper intends to present Well-being is varies from person to person and might include aspects of mental, physical, emotional, spiritual, social, economic, and professional fulfillment. Focusing on those areas of women's well-being is a crucial goal for their wellness. Some aspects of women's health that are disrupted include urine incontinence, gastrointestinal stress, reproductive and hormonal issues, and bone health. Women's health is a significant issue since discrimination against them persists in society to this day. The World Health Organisation reports that more than 800 women pass away during pregnancy and childbirth every day. Women and girls face new health crises and obstacles, which interferes with their access to essential support services and medical care. Women score highest in terms of wellbeing and health difficulties, with a higher risk of ovarian cancer, breast cancer, heart disease, depression, and anxiety. The health problems that women face include some serious illnesses that can significantly impact their overall health and well-being. Early treatment is available for conditions including breast and ovarian cancer. If a woman experiences severe abdominal discomfort, breast lumps, or irregular bleeding, she should consult a physician. A child's physical, mental, intellectual, social, and emotional well-being is referred to as their health; it goes beyond simply being free from illness or disability. Healthy children are raised in homes, communities, and surroundings that allow them to develop to the best of their abilities.